He moana pukepuke: navigating gender and ethnic inequality in early career academics' conference attendance. Issue 1 (2nd January 2020) - Timperley, Claire; Sutherland, Kathryn A.; Wilson, Marc; Hall, Meegan
ABSTRACT: Drawing on data collected in a cross-disciplinary survey of early-career academics (ECAs) in New Zealand, this article explores the factors influencing ECA conference attendance. Our conceptual framework uses conference attendance as the dependent variable and measures gender, ethnicity, family responsibilities and workload. Three key features affect conference attendance: demographic characteristics (background features and prior experiences that affect an academic's willingness and ability to attend), accessibility (constraints to attending, such as financing, family responsibilities, institutional support or teaching commitments) and purpose (the value placed on attending conferences by the individual, the institution, or the discipline). In particular, we identify differences for women, Indigenous people, and those born overseas with respect to their ability to navigate and their inclination to attend national and international conferences.